SP0188 SAPHO – AN ADULT PERSPECTIVE. (June 2019) - Assmann, Gunter
Abstract : Background: The acronym SAPHO has been introduced to describe a syndrome in adolescents and adults suffering from synovitis (arthritis), acne, pustulosis, hyperostosis, and non-bacterial osteitis preferentially in the sternal region. Currently, this also includes the entity CNO with non-bacterial chronic recurrent multifocal osteomyelitis (CRMO) in cases which primarily occur in adult age. Objectives: The diagnostic certainty of SAPHO syndrome in case of incomplete presentation of the clinical features has been unclear so far. Furthermore, the treatment approach of SAPHO syndrome is difficult because the etiology remains unknown, although a reactive infectious osteitis in genetic predisposed subjects seems appealing. Methods: Here we present relevant case series of SAPHO patients which should elucidate the relevance of different diagnostic procedures and treatment options. It has been noted, however, that particularly in respect of the use of antirheumatic drugs case series with predominantly small numbers of SAPHO patients suggest different treatment approaches. Results: The diagnosis of SAPHO syndrome is made not only in the full picture of the disease according to the acronym, but also in non-bacterial and non-malignant osteitis with hyperostosis with simultaneous or delayed onset of acne, psoriasis and/or PPP. In addition, the primary manifestation of CNO in adulthood is nowadays classified as SAPHO syndrome. Recent studies have previously confirmed the usefulness of skeletal scintigraphy in 2 phases as a diagnostic. Imaging with MRI is frequently used preferentially for the assessment of osteitis activity, CT for the assessment of destruction and hyperostosis. The CT-guided biopsy of the lesion should be performed in solitary manifestation of osteitis. Basically, SAPHO syndrome has a high impact on patients' general health resulting in high burden of disease. There are many approaches to drug therapy, but only a few have been investigated in larger case series - none of them as controlled studies. Smaller case series of less than 10 patients reported limited efficacy of DMARD with MTX, azathioprine, or ciclosporin. Studies with larger case numbers show a moderate efficacy of bisphophonates as well as TNF-alpha blockers. A short-term but not sustained effect has been demonstrated for the antibiotic azithromycin, as well as for steroids per os or as infiltration into osteitis. Referring to the treatment approach in SpA newly approved biologicals with IL-17 or IL-12/23 blocking effects demonstrated promising results in individual case reports of SAPHO patients. Conclusion: Modern diagnostic imaging methods are increasingly being used for SAPHO syndrome. The selection of potentially effective drugs for SAPHO syndrome has increased. However, prospective studies to develop guidelines for the diagnosis and therapy of SAPHO syndrome are still lacking. Until further notice, the therapy is based on the recommendations for psoriatic arthritis or spondyloarthritis. Disclosure of Interests: None declared